PENGARUH METODE GROUP INVESTIGATION TERHADAP AKTIVITAS BELAJAR MUATAN IPS SISWA KELAS IV SDN 3 SAMBELIA TAHUN PELAJARAN 2020/2021 - Cici Monica Astuti Maja; Nurhasanah Nurhasanah; Husniati Husniati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
This study aims to determine the effect of the group investigation method on the social studies content of fourth grade students of SD Negeri 3 Sambelia in the academic year 2020/2021. The type of research used is quantitative research with the ex post facto method. The population in the study were all fourth grade students of SD Negeri 3 Sambelia. Determination of the sample used in this study using saturated sampling technique, in order to obtain a sample of 41 students. The data collection method used in this study was a questionnaire method. Data analysis was calculated using SPSS 16.0 for windows. The data analysis begins with a normality test using the Kolmogorov Smirnov one sample formula, the results of the normality test show that the group investigation method data is 0.169 and the students' social studies content learning activity is 0.898, both values ​​are greater than 0.05 which means that the two variables are normally distributed. The data linearity test with the acquisition of a significance value in the Deviation from Linearity column of 0.061> 0.05, which indicates that there is a linear relationship between the group investigation method on student social studies content learning activities. Testing the hypothesis using the t test, the results of the analysis show that the value of tcount 2.340> ttable 2.022, it can be interpreted that there is an influence between the group investigation method on the social studies content learning activities of fourth grade students of SD Negeri 3 Sambelia. Then test the determinant coefficient by obtaining data on the Adjusted R Square column of 0.101 or 10.1%, which means that the group investigation method has a low effect on the learning activities of social studies content for fourth grade students of SD Negeri 3 Sambelia.